KREATIVITAS SEBAGAI UPAYA MENINGKATKAN KUALITAS DAN MELESTARIKAN TARI ADOK PADA MASYARAKAT SOLOK SUMATERA BARAT - Yarlis; Risnawati; Adjuoktoza Rovylendes (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
the accompaniment of traditional ceremony. Nowadays, this dance is less desirable by people development by conducting creativity or more interesting innovation by developing aspects found in dance composition knowledge. General purpose of this research is improving Adok dance quality by applying dance composition knowledge that results on new product and then this new product is given back to society through tourism program. Method used in achieving this research purpose is qualitative and R&D methods, by using four chosen scientific approach namely: (1) Observation, (2) Library research, (3) Development, by applying R&D method (4) Experimental study and marketing, as effort to promote and preserve traditional art so it through tourism program. This research is scheduled in three stages. First stage is conducted in 2016 by doing observation, searching literature and collecting data related to Adok dance. Second one is conducted in 2017 by doing creativity in form and technique development/innovation according to choreography aspects so that new product of Adok dance is born. Third stage is conducted in 2018 in which the new product of Adok dance is given back to its supporting society through tourism program. This research result can be used by local government, particularly tourism office of Solok city, as teaching material in the subjects of Dance Knowledge, Performing Arts, Dance History, and Traditional Dance in the Faculty of Performing Arts, Dance Department, Indonesia Art Institute of Padangpanjang, West Sumatra.